Structural Components of the Dynamic Model of the System of Training Primary Education Masters - Yuldashev Rustam Elmurodovich (Genius Publishing Group, 2022)
The article analyzes experiments on the structural components of the dynamic model of the system for preparing masters of primary education.
Keywords: Implicit; component; education; master